Dose tapering to withdrawal stage and long‐term efficacy and safety of hetrombopag for the treatment of immune thrombocytopenia: Results from an open‐label extension study. (15th December 2021) - Mei, Heng; Liu, Xiaofan; Li, Yan; Zhou, Hu; Feng, Ying; Gao, Guangxun; Cheng, Peng; Huang, Ruibin; Yang, Linhua; Hu, Jianda; Hou, Ming; Yao, Yazhou; et al.
Abstract: Background: The efficacy of hetrombopag in Chinese patients with immune thrombocytopenia (ITP) has been demonstrated in a randomized, double‐blind, placebo‐controlled, multicenter, phase III trial (NCT03222843). Objective: This study aimed to report comprehensive data on a ≤6‐week dose tapering to withdrawal (Stage 3) and an additional 24‐week long‐term extension period (Stage 4) in this phase III trial. Patients/Methods: Patients who fulfilled the screening criteria were eligible to enter Stage 3 or 4. During Stage 3, hetrombopag was gradually tapered to withdrawal. During Stage 4, hetrombopag treatment was initiated at 2.5, 3.75, 5, or 7.5 mg once daily. The efficacy endpoints during Stage 3 or 4 and the safety profile during the entire treatment period were reported. Results: Among 194 patients who entered Stage 3, 171 (88.1%) relapsed. The median time to the first relapse since the start of Stage 3 was 15.0 days (95% CI, 14.0–16.0). In Stage 4, 144 (42.5%) patients responded at ≥75% of their assessments and 254 (74.9%) patients achieved platelet count ≥30 × 10 9 /L at least once, which was at least twice their baseline platelet count in the hetrombopag group ( n = 339). The most common adverse events were upper respiratory tract infection (53.1%), thrombocytopenia (27.1%), and urinary tract infection (21.2%) in the hetrombopag group. Conclusion: The majority of patients who experienced dose tapering to withdrawal experienced a relapse. Long‐term treatment with hetrombopag was effective in increasing and maintaining platelet count within the desired range in Chinese adults with ITP. Hetrombopag was well tolerated.